A preliminary study of the solubilization of wool and separation of soluble wool into protein classes : this thesis was presented in part fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Jull, Adrian Clifford (Massey University, 2000)
The processing of natural products into new added value products is of importance to New Zealanders and the economy of their country. Chemical processing of wool into potential new products would be greatly assisted by separation of wool proteins into protein classes. A preliminary study of solubilizing wool protein by reduction and oxidative sulfitolysis of the cystine disulfide linkages was carried out. Oxidative sulfitolysis was used to obtain stable soluble wool protein for further investigation. Assays were developed for analysis of the effectiveness of chemical processing of the wool. To separate dissoluted wool proteins from dissolution reagents ultrafiltration was used to obtain desalted soluble wool protein. Data are reported on foam fractionation conditions of pH, concentration, sparging gas and desalting. Wool was reduced and solubilized using sodium sulfide. The soluble product was processed under nitrogen and proved unstable in air. Thin films were produced from desalted reduced wool protein solutions by auto oxidation on exposure to air. Sulfonation of wool cystine to S-sulfokerateine proteins routinely achieved stable soluble product of 60 % yield. Films were prepared from the desalted soluble sulfonated wool protein. The most efficient solubilization was achieved by reduction with sulfide ion, with 70+ % yields from a low wool to liquor ratio of 1:10. The lack of stable soluble product hampered down stream processing and oxidative sulfitolysis was chosen for further investigation in this study. Assays of wool protein proved problematic with interference of dissolution reagents. The bicinchoninic acid assay provided considerably elevated total protein values compared to the biuret and gel permeation chromatography methods, making it unsuitable for wool protein analysis. The biuret assay was found to have variable results. Dissolution of wool by > 50 % produced biuret results in close agreement to total protein values obtained from protein dry mass after dialysis. A method for total protein assay using gel permeation chromatography with UV detection was developed Gel permeation resulted in separation of protein from the dissolution reagents and detection of the eluting protein peak at 200 nm. Total protein determination by gel permeation was reliable and consistent and was able to be applied to all the protein solutions analyzed. Excellent correlation was achieved between gel permeation and protein dry mass analysis. Separation to enable identification of protein classes in the processed material was attempted using capillary electrophoresis and capillary gel electrophoresis. Preliminary investigations established suitable capillary electrophoresis conditions for further study of wool protein. Gel permeation using Sephadex G-75 and Superdex 75 did not yield separation of protein to a standard comparable to that achieved by ID SDS-PAGE. Proteins are surface active and therefore represent natural self-foaming agents. Foam fractionation was examined with dissoluted and desalted wool protein Optimum foam fractionation conditions were established at pH 7.8 - 8.2 and protein 1-3 mg/mL concentration. Protein was precipitated from desalted soluble wool protein using foam fractionation and represents a potential method for separation of wool proteins from solution. Manipulation of desalted wool protein solutions to surface tension minima defined by pH, holds promise of separation of wool proteins into groups. These groups will share isoelectric points in common and possess similar hydrophobic interactions. Whilst these groups may cut across the established protein classes, products from these groups will possess distinct shared properties. Refinement of the foam fractionation technique utilizing the grouping of surface active wool proteins, holds scope for protein separation with further development.
Keywords: Solubilization; Proteins; Wool composition